A systematic review on the investigation of optimal operating conditions of the reverse osmosis process in nitrate removal from drinking water - Fatemeh Zirrahi; Mahdi Hadi; Ramin Nabizadeh Nodehi; Esfandiar Ghordouei Milan; Parnia Bashardoust; Samaneh Abolli; Mahmood Alimohammadi (Results in Engineering, 2024)
During the last few decades, several global crises including limited water resources, massive contamination of water resources, and available water bodies with high TDS have made researchers use new and advanced technologies to improve water quality. Since RO technology is proven to be a capable method in the removal of both anions and cations from water, the current systematic review was conducted to evaluate the efficiency of RO to provide a suitable approach for managers and health officials to solve the problem of increasing nitrate concentrations in drinking water sources. 2743 articles and theses were included in the primary search. Following screening and final restrictions that took the goals of the review into account, 61 presented studies were chosen for coverage. Among the 61 selected articles and theses, 54% of studies were conducted on groundwater, 25% of studies used BW-high rejection membrane, 58% of studies used polyamide membrane, 59% of them used spiral wound modules. The mean concentration levels of NO3 in the inlet-outlet and nitrate removal rate of the RO process were 145.7 and 20.8 mg/L and 85.03, respectively. Based on the proposed regression model, various variables including the type of environment to be treated, nitrate concentration at the inlet of the treatment system, the type of applied membranes, the area of the membranes and the pH value of the water showed a significant relationship with the concentration of nitrate at the outlet of the treatment system. The optimal conditions were the type of brackish water-low differential pressure membrane, the basic materials used for the manufacture of the membranes like polyamide/single-wall carbon nanotubes, the operating pressure of 5 bar, the area of the membrane of 2.6 m2 at a pH of 7.